On the existence and uniqueness of a solution of the problem of uniform SK-spline-interpolation - Serdyuk, A. S. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We establish necessary and sufficient conditions for the existence and uniqueness of generalized interpolatingSK-splines with a uniform distribution of interpolation points.